Low-energy signatures of charge and spin fluctuations in Raman and optical spectra of the cuprates - Caprara, Sergio; Enss, Tilman (Arxiv, 2008)
We calculate the optical and Raman response within a phenomenological model of fermion quasiparticles coupled to nearly critical collective modes. We find that, whereas critical scaling properties might be masked in optical spectra due to charge conservation, distinct critical signatures of charge and spin fluctuations can be detected in Raman spectra exploiting specific symmetry properties. We compare our results with recent experiments on the cuprates.